2004
DOI: 10.2202/1949-6605.1395
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Student Learning and Development: A Shared Responsibility

Abstract: O Historically, student affairs professionals focused their work almost exclusively on undergraduate students. Doctoral faculty remained focused on the comprehensive needs of doctoral students. However, this situation is changing. Due largely to growth in numbers and diversity of graduate students, student affairs professionals at colleges and universities across the country are increasingly redefining their visions and their roles to include graduate students, including doctoral students.This research study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Limited research to date has focused on specific support services for graduate students, such as professional-development (Holaday, Weaver, & Nilson, 2007), counselling services (Oswalt & Riddock, 2007), thesis writing support (Elgar, 1998), housing (Mills, 2006), orientation (Polson, 2003), funding (Strayhorn, 2010), and pan-university institutional initiatives (Bair, Haworth, & Sandfort, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Limited research to date has focused on specific support services for graduate students, such as professional-development (Holaday, Weaver, & Nilson, 2007), counselling services (Oswalt & Riddock, 2007), thesis writing support (Elgar, 1998), housing (Mills, 2006), orientation (Polson, 2003), funding (Strayhorn, 2010), and pan-university institutional initiatives (Bair, Haworth, & Sandfort, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Greenlaw et al (1997) Bair et al (2004) supported the assertion that scholarly activity and research productivity was a major role with data from a nursing professor who stated, "Our most important responsibility as faculty is to be role models for doing research" (p. 715). An administrator supported the assertion of the importance of advising and mentoring students as a mechanism to integrate students into the profession:…”
Section: )mentioning
confidence: 85%
“…The student stated, "They had a 'we accept you, we want you attitude,' not we are trying to weed you out" (p. 717). Bair et al (2004) concluded that this role helped many students feel integrated into their programs.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations